Racial/ethnic differences in mental health treatment received among people with comorbid cardiometabolic and depressive symptomology: National Health and Nutrition Examination Survey, 2017 to March 2020 Pre-Pandemic. - Tyra Dark; Rachel Harris; Desiree Burns; Jacob Chernicky; Laura Reid-Marks; George Rust (PLoS ONE)
Background Individuals with chronic physical conditions and comorbid mental illness have increased probability of adverse health outcomes. As minority populations have limited access to both medical care and culturally appropriate mental health services, having a comorbid mental health condition can further impede their ability to manage chronic conditions and widen racial disparities in health outcomes. Further, racial/ethnic disparities in treatment patterns are likely to exacerbate disparities in adverse health outcomes. Objective To identify the racial/ethnic mental health treatment patterns among individuals with cardiometabolic and depressive symptomology co-occurrence. Methods This study utilized National Health and Nutrition Examination Survey data, 2017 to March 2020 Pre-Pandemic. The primary analysis was an adjusted linear logistic regression analysis of race/ethnicity, comorbidity status and mental health treatment type. Regression models were estimated to determine the likelihood of receiving counseling and medication therapy, and to determine if the likelihood is associated with race/ethnicity. Results Primary findings indicate that depressive symptomology only was the most common designation and fewer than half of persons received any mental health treatment. Across all racial/ethnic groups, receiving no mental health treatment was the most common designation. Sixty-one percent of Non-Hispanic White persons and more than three out of four Hispanic and Non-Hispanic Black persons with only depressive symptoms received no mental health treatment. Adjusted regression analyses revealed that participants with comorbid cardiometabolic and depressive symptomology have 28% lower odds of receiving combined mental health professional and medication therapy than participants with depressive symptomology only. Conclusions Simultaneously treating both mental illness and cardiometabolic symptoms properly is complicated, but there may be untapped synergies in treating both concurrently. Therefore, to achieve favorable health outcomes, policy should be implemented to optimize clinical treatment by addressing aspects of both conditions in an integrated approach and may need to be culturally tailored to be effective.